in vivo Study of Central Nervous System Depressant Effects and Muscle Relaxant Activity of Methanolic Extract of Galphimia gracilis Leaf on Swiss Albino Mice - Shankar Rao Garige1, Baba; Srisailam2, Keshetti; Maheshwara Rao Vattikuti3, Uma (Asian Journal of Chemistry, 2016)
This study assesses the central nervous system depressant effects and muscle relaxant activity of methanolic extract of Galphimia gracilis leaf in Swiss albino mice employing models like open field test, hole-board test, sodium pentobarbital-induced sleep test, pentylenetetrazole induced convulsions, picrotoxin-induced convulsions, rota rod test and grip strengthening test. The LD50 results of the extract was found to be > 2000 mg/kg. The extract exhibited significant (P £ 0.001) effects in both the open field test and hole-board test. The extract at 100, 200 and 400 mg/kg doses extended the duration of sleep induced by sodium pentobarbital (40 mg/kg) and also delayed the onset of seizures induced by pentylenetetrazole (90 mg/kg) and picrotoxin (10 mg/kg) respectively. The extract also exhibited significant (P £ 0.001) effects in Grip strengthening test and Rota rod test. The study concludes that the methanolic extract of Galphimia gracilis leaf has significant depressant activity and muscle relaxant effects.